Desain dan Implementasi E-Book Interaktif sebagai Media Pembelajaran Sejarah untuk Meningkatkan Prestasi Belajar Siswa MAN Dompu - Sumiyati Sumiyati; Sulaiman Sulaiman; Rizzaludin Rizzaludin; Ratna Ratna (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to test the validity, practicality and effectiveness of Interactive E-BOOK teaching materials in improving reading literacy of grade XI students of MAN Dompu. Interactive E-BOOK teaching materials are two-dimensional visual learning media that are systematically designed to support the learning process. This research uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The research sample amounted to 33 students from a population of 192 students selected through purposive sampling technique. Data were collected through questionnaires, observations, tests, and documentation, then analyzed to measure the validity, practicality, and effectiveness of the media. The results of validation by two experts showed a validity level of 89% (category “Very Valid”). The practicality of the media obtained a percentage of 87.1% (category “Very Practical”). The test results showed an increase in learning completeness from 45% in the pretest to 87% in the posttest. Thus, the Interactive E-BOOK teaching materials were declared valid, practical, and effective in improving students' reading literacy.